Attachment Styles of Adolescent Substance Users - Cömert, Itır Tarı; Ögel, Kültegin (Addicta: The Turkish Journal on Addictions, 2014)
An individual’s attachment style develops during infancy and influences that individual’s adulthood. During adolescence, as attachment is replaced by individual freedom, adolescents are likely to engage in risky behavior. This research study, which investigates the relationship between adolescents’ attachment styles and substance use, was conducted in November and December 2012 with a sample of 1,095 (51.2%) male and 1,045 (48.8%) female students in Istanbul, Turkey. The students were selected using a multistage cluster sampling method and were of various socioeconomic levels. The data were collected through administration of a questionnaire in 86 high-school classrooms. The results showed that 10% of the students used some type of substance, 9.7% used multiple substances, and 3.8% habitually used cannabis. The dismissing attachment style was most prevalent, displayed by 48% of the students. Significant correlations were found between substance use and both the dismissing and preoccupied attachment styles. Continuous use of cannabis was highly correlated with lack of a secure attachment style.